Sustainable development and fair trade-A systematic review of the main research published between 2010 and 2022 (LACCEI, 2024)
Currently, the impacts caused by sustainable development and fair trade in agriculture are favorable for the growth of production. The objective of this research was to determine the current trends on the commercial, environmental, and economic impact of sustainable development and fair trade in the agricultural sector during the period 2010 - 2022. The systematic review of literature (SRL) was used as a methodology, giving as a result, the choice of 40 sources for the analysis of this research. The results had determined that there is a greater use of the qualitative approach in refereed publications on the field of study. In addition, concluded that the effort of economic, public, private, and socioeconomic actors is required to achieve a synergy to induce a joint transformation of the agricultural sector. Likewise, research trends determine that there is a positive commercial impact of the usage of fair trade and sustainable development in the world that caused a greater commercial growth in the agricultural sector.